Theoretical Study of the Solvatochromism of a Donor-Acceptor Bithiophene - Caroli-Rezende, M; Dominguez-Caru, M (2013)
The solvation and the solvatochromic behavior of the 5-(methylthio)- 5?-nitro-2,2?-bithiophene 1 in diethyl ether, dichloromethane, acetonitrile, methanol and formamide was theoretically investigated with an iterative molecular and quantum mechanics (QM/MM) approach. Calculated longest-wavelength solvatochromic absorption band of 1, obtained as averages of statistically uncorrelated configurations, including the solute and explicit solvent molecules of the first and second solvation layer, were in excellent agreement with the experimental results. [Figure not available: see fulltext.] © 2012 Springer-Verlag.